Increasing Local Government E-Government Innovation In Achieve Good Government - Ika Widiastuti; Uchaimid Biridlo'i Robby; Pandu Adi Cakranegara (Budapest International Research and Critics University, 2022)
In order to support government programs to compete and have regional innovations as a form of creativity and ability of local governments in Indonesia to create innovations that can improve social welfare. Innovative areas are the implementation of local economic development based on local wisdom and capabilities that are based on regional resources. E-governmentaims to achieve good government through the use of technology, changes in the government system and community participation. The success of e-government innovation is HR, leadership and community participation. Collaboration and e-literacy are strategies in e-government. Collaboration is cooperation in alleviating financial problems. E-literacy is the ability of human resources in understanding learning media that aims to increase community participation. The purpose of this research is to know and understand the improvement of e-government innovation in achieving good government in local government. The method used is literature study.The results of the study are the low regional innovation so that it has an impact on the implementation of e-government.With the existence of e-government innovation, it is hoped that it can be applied in local governments for Indonesia which is advanced and rich in regional innovation and the achievement of good government.